Madrasah Politics and Transnational Educational Networks in Southeast Asia: A Systematic Literature Review - Wastuti; Muljono Damopolii; Muchammad Eka Mahmud; Awaluddin Hidayatulloh (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
Madrasahs are among the Islamic educational institutions that have experienced significant development in Southeast Asia over the past two decades. These changes have taken place alongside increasing state involvement in the governance of Islamic education, curriculum transformation, and the strengthening of transnational networks connecting Islamic educational institutions in the region with the broader Muslim world. In this context, madrasahs function as arenas of interaction between state policies, religious identity, and the dynamics of globalization in Islamic education. This study aims to analyze the dynamics of madrasah politics and the forms of transnationalism that influence the development of Islamic education in Southeast Asia. The research employs a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework. Data were collected from the Scopus database and thematically analyzed across 19 articles that met the inclusion criteria. The findings indicate that madrasah politics in Southeast Asia primarily focus on institutional regulation, curriculum reform, the integration of Islamic education into national education systems, and the construction of Muslim identity. Meanwhile, the dimension of transnationalism is reflected in curriculum transfer, ulama mobility, the strengthening of Arabic language instruction, the internationalization of Islamic education, and the diffusion of educational models across countries. The study concludes that the development of madrasahs in Southeast Asia is shaped by the dynamic interaction between state policies, the needs of Muslim communities, and global Islamic educational networks. Madrasahs serve as key institutions in shaping the direction of Islamic education that is responsive to social, national, and global dynamics.